Ernährung & Sport - Wartha O; Lämmle C; Kobel S; Wirt T; Steinacker JM (Deutsche Zeitschrift für Sportmedizin, 2017)
Background: Physical activity (PA) is important for healthy development. During childhood, PA is realised by unstructured play and instructed sports. Few children achieve the recommended90-120 minutes of daily PA. Interventions promoting PA have to start early and have to combine behavioural and situational approaches.Research question: How is the PA part of the intervention programme Join the Health Boat Primary School designed and whatare its aims?Methods: The school-based intervention rests on Bartholomews Intervention Mapping approach. Results: Main aspects of the interventions PA part are increase of daily PA and reduction of screen media use. The programme combines behavioural and situational approaches. Materials were developed for all primary school grades. The teacher-centred intervention comprises of 20 teaching units per year, 56 cards for daily activity breaks, parent materials and teacher training courses. Besides an aim to transfer knowledge, presentation of action alternatives is key. The interventions motor aspect focuses on conditional and coordinative skills, parents and teachers are also targeted by this intervention in order to embed PA in childrens daily routines. Discussion: School is an ideal setting for interventions to promote PA. It is possible to transfer knowledge and realise PA. The interventions motor aspect is chosen deliberately,since low motor skills are associated with low PA levels. Furthermore, elementaryschool age is a crucial phase for motor skills development.KEY WORDS: Physical Activity, Prevention, Intervention, Physical Performance, Evaluation